Investigation of Antioxidants's Antimutagenic Effects by The Ames Test - BECEREN, AYFER (MARMARA UNIV, FAC PHARMACY, 2017)
Nowadays, several test systems have been developed in order to observe the mutagenic effects of chemical agents which play crucial roles in human health. The Ames Test is one of these test systems. With the Ames Test, some bacterial mutants have been discovered to investigate the mutagenic effects of the chemicals. Various strains of Salmonella typhimurium are one of the groups of the bacterial mutants in question. The aim of this study is to investigate possible antimutagenic effect of Pelargonium sidoides which have an antioxidant effect towards carcinogenic substance called 2-aminofluorene by Ames/Salmonella/Microsome test kit in the absence and presence of metabolic activation. TA 98 and TA 100 strains were used in these experiments. TA 98 is designed for frame-shift mutagens and TA 100 is designed for base-pair mutagens. The antimutagenic activity was screened in two groups with or without S9 metabolic activation. The results were evaluated the mean average values and compared with positive and negative controls. In conclusion, it was shown that Pelargonium sidoides have antimutagenic effect towards TA 98 and TA 100 without S9 metabolic activation (p >= 0.05) but have no antimutagenic effect towards TA 98 and TA 100 with S9 metabolic activation (p <= 0.05).
Keywords: Ames test; antioxidant; Pelargonium sidoides; S9 fraction; mutagenicity; PELARGONIUM-SIDOIDES; MUTAGENICITY; ASSAY; ANTIBACTERIAL; PERFORMANCE; RENIFORME; RESPONSES